The seasonal changes in the position of the upper boundary of the Black Sea hydrogen sulfide zone due to the nature of the dynamic processes development - Р.Р. Белевич; О.Р. Андріанова; М.І. Скіпа (Геофизический журнал, 2022)
The position and seasonal fluctuations of the depth of the maximum water salinity gradient in the Black Sea in the upper 150 m layer (halocline), which is interpreted as the upper boundary of the hydrogen sulfide layer in the sea, were estimated based on the analysis of climatic data of the vertical distribution of salinity for the period 1903—1982. Seasonal maps of the depth of this boundary in the water area of the sea were constructed, and extrema (axes of maximum and minimum) were identified. Features of dynamic processes in the Black Sea were estimated by the position of the axes of the convergence and divergence zones, which correspond to the values of the maximum and minimum in the field of the considered characteristic. Water temperature and salinity maps in isolines with extremum axes highlighted on them — the positions of the vergence zones axes were built at this depth in a similar way. Thus, ideas have been obtained where the position of the upper boundary of the hydrogen sulfide layer should be expected in a specific season and region.